Influence of Corn Cob Ash-Silica Fume Blend on the Mechanical and Durability Properties of Concrete - Otieno, Linda Akoth; Abuodha, Sylvester; Mumenya, Siphila; Munyua, Muthomi (LPPM Universitas Andalas, 2023)
— This research explored the feasibility of corn cob ash-silica fume blend in the production of pozzolanic cement to produce High-Performance Concrete. The cement in concrete was partially replaced by corn cob ash-silica fume blend in 5,10,15 and 20% by weight of cement and was compared to a control mix of 0% replacement. An intelligent mix design, Densified Mix Design Algorithm (DMDA), was used to effectively reduce both water and cement content. In order to create high strength and workability, a polycarboxylate-based super plasticizing admixture was utilized in conjunction with a low water binder ratio of 0.35. Compressive strength was appraised to determine the mechanical properties at days 3,7,14,28 and 56 to determine the optimum percentage replacement and compared to the control at the specific ages. With the optimum percentage replacement, the flexural test was investigated at 28 days. Water absorption and electrical resistivity tests were also investigated as potential indicators of durability. All of the blends that included corn cob ash and silica fume produced a higher strength than the control except 15 and 20%, with 10% replacement yielding a cube strength of 61 MPa at day 56.